Efficacy and safety of pentoxifylline combination therapy in major depressive disorder: a randomized, double-blind, placebo-controlled clinical trial. (12th March 2021) - Farajollahi-Moghadam, Mostafa; Sanjari-Moghaddam, Hossein; Ghazizadeh Hasemi, Maryam; Sanatian, Zahra; Talaei, Ali; Akhondzadeh, Shahin
Abstract : In this randomized, double-blind, placebo-controlled clinical trial, we assessed the efficacy and safety of pentoxifylline combination therapy with sertraline in treatment of major depressive disorder (MDD). A total of 56 patients with MDD were assigned into two parallel groups to receive sertraline (100 mg/day) plus placebo or sertraline (100 mg/day) plus pentoxifylline (400 mg three times daily) for six weeks. Patients were evaluated with the Hamilton rating scale for depression (HAM-D) at baseline and weeks 2, 4 and 6. The sertraline plus pentoxifylline group demonstrated greater improvement in HAM-D scores from baseline to all three study time points ( P = 0.013, 0.007 and 0.016 for week 2, 4 and 6, respectively). Response to treatment rate was also significantly higher in the sertraline plus pentoxifylline group compared to the sertraline plus placebo group at week 4 [57.1 vs. 21.4%, P = 0.013] and the study endpoint [96.4 vs. 57.1%, P = 0.001]. However, the remission rate, time to remission and time to treatment response did not show any significant difference between trial groups. Our findings support the efficacy and safety of pentoxifylline combination therapy in patients with MDD.